The educational philosophy of Rui Barbosa and Lourenço Filho regarding the intuitive teaching method (1890–1930) (Patrimônio e Memória, 2018)
The aim of this article is to discuss the educational thinking of Rui Barbosa and Lourenço Filho regarding the intuitive teaching method from 1890 onwards, within the context of the reform of the Brazilian state school system. It is worth noting that the former reflected on educational issues that arose during the transition from the Empire to the Republic, whilst the latter was one of the leading figures of the New School movement in Brazil. The analysis aims to highlight the similarities and differences between these two perspectives in order to underscore the ruptures and (dis)continuities in these schools of thought in Brazil during the period spanning the First Republic. Furthermore, this article seeks to draw connections between the differing perspectives of these intellectuals on the intuitive teaching method during the period from 1890 to 1930.